Four new species of Hisonotus (Siluriformes: Loricariidae) from the upper rio Uruguay, southeastern South America, with a review of the genus in the rio Uruguay basin - Carvalho, Tiago P.; Reis, Roberto E. (Zootaxa, 2009)
Four new species of Hisonotus are described from the upper course of the rio Uruguay basin in Brazil: Hisonotus iota from the rio Chapecó drainage; Hisonotus leucophrys from rio Rancho Grande and rio Ariranhas; Hisonotus megaloplax from the rio Passo Fundo drainage; and Hisonotus montanus from the rio Canoas drainage. The species Epactionotus aky, described from the arroyo Yabotí-Guazú drainage in Argentina, is transferred to Hisonotus and rediagnosed. Hisonotus candombe is considered a junior synonym of H. ringueleti. The new taxa, together with H. nigricauda, H. ringueleti, H. charrua, and H. aky represent the genus Hisonotus in the rio Uruguay basin. A taxonomic key for Hisonotus in the rio Uruguay basin is provided. Their distributions are discussed under biogeographic patterns previously proposed for the rio Uruguay basin.